Biomarkers and biosensors : detection and binding to biosensor surfaces and biomarkers applications - Sadana, Ajit, 1947-; Sadana, Neeti (Elsevier, 2015)
Biomarkers and Biosensors offers thorough coverage of biomarker/biosensor interaction, current research trends, and future developments in applications of drug discovery. This book is useful to researchers in this field as well as clinicians interested in new developments in early detection and diagnosis of disease or the mode of operation of biomarkers. Biomarkers and Biosensors also emphasizes kinetics, and clearly delineates how this influences the biomarker market. Offers thorough coverage of the kinetics of biomarker interaction with the biosensor surfaceProvides evidence-based approach to.